Methods of learning and studying economic sciences - Ortikov, Eldor; Avliyakulov, A; Avazov, A (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Economic theory is inextricably linked with other economicsciences. First, it enriches them with new conclusions by summarizing theirachievements. Second, it facilitates their development by arming them with conclusions about general economic theory.Economic theory basically performs three functions:a) understanding of the laws of economics, economic education,economic literacy;b) to serve as a basis for other economic disciplines, to be theirtheoretical basis;c) to provide practical recommendations on economic policy, to providea theoretical basis for policy development.